Harmonisasi Implementasi Kebijakan Publik Dalam Penanggulangan Kemiskinan di Kabupaten Gorontalo - Nadila, Wahidatun; Ilato, Rosman; Sulila, Ismet (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the harmonization of public policy implementation in poverty alleviation in Gorontalo Regency. The main focus of this research is how planning, implementation and evaluation of policies can be coordinated harmoniously among regional organizations. Apart from that, this research also identifies factors that influence the harmonization of public policy implementation, including communication, resources, disposition and bureaucratic structure. This research uses a qualitative approach with in-depth interviews with informants. The research results show that the implementation of poverty reduction policies still faces challenges in the form of weak coordination, limited resources, and inconsistencies in policy implementation. The conclusion of this research is that harmonization of public policy implementation in poverty alleviation can be improved through better communication, strengthening resources, and reform in bureaucratic structures.